Analisis Monosit dan Neutrofil pada Pasien Tuberkulosis Paru di Puskesmas Wonorejo Samarinda. - Julia Saputri, Maulida; Fadilah, Nur; Trianditha, Rinanda; Srilestari, Titik (Jurnal Kesehatan Mahardika, 2025)
Tuberculosis (TB) remains a significant global health concern, with the immune response involving key roles for monocytes and neutrophils. Analysis of immune cells, such as monocytes and neutrophils, is crucial for understanding the host response to TB infection and for monitoring treatment effectiveness. This cross-sectional study analyzed the distribution of monocyte and neutrophil counts among 17 pulmonary TB patients in Puskesmas Wonorejo Samarinda from January-April 2024. The collected data were analyzed descriptively. Results showed that 64.70% of patients had elevated monocyte counts, while 35.30% had normal monocyte levels. For neutrophils, 41.20% of patients had normal counts, 17.60% had increased counts, and 41.20% had decreased counts. The predominance of monocyte elevation and the heterogeneous neutrophil response underscore the importance of these cells as potential biomarkers for TB monitoring and prognosis. Strengthening the use of these parameters may improve clinical management and outcomes for TB patients.